Pervious concrete and preparation method thereof

By using materials such as enveloped magnesium carbonate and enveloped sustained-release ammonium chloride in permeable concrete, the problem of porosity blockage of permeable concrete is solved, and good water permeability and strength after long-term use is achieved.

CN119797833APending Publication Date: 2025-04-11BEIJING XINJIANGFENG BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411789151.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-11
Filing Date
2024-12-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

After long-term use of existing water-permeable concrete, its porosity is easily clogged by debris and dust, affecting its water-permeable effect.

Method used

The filled particles consisting of enveloped magnesium carbonate, enveloped sustained-release ammonium chloride, hydrophobic zeolite and basalt particles are used to produce magnesium chloride dissolved in water through the slow dissolution of magnesium carbonate in water and the sustained-release reaction of ammonium chloride to form magnesium chloride dissolved in water, thereby promoting the discharge of dust and impurity particles and maintaining porosity and water permeability.

Benefits of technology

It effectively avoids the blockage of porosity, ensures the permeability and strength of permeable concrete after long-term use, and prevents freeze-thaw cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174884880000101
    Figure BDA0005174884880000101
Patent Text Reader

Abstract

The invention relates to the field of concrete, and particularly discloses pervious concrete and a preparation method thereof. The pervious concrete is prepared from the following raw materials in parts by weight: 300 to 400 parts of cement, 1000 to 1400 parts of coarse aggregate, 80 to 120 parts of water, 20 to 40 parts of fly ash, 20 to 40 parts of mineral powder, 3 to 4 parts of a water reducing agent, 10 to 20 parts of hydrophobic fibers and 14 to 25 parts of filling particles, the filling particles consist of coated magnesium carbonate, coated slow-release ammonium chloride, hydrophobic zeolite and basalt particles in a mass ratio of 1: (1-1.5): (2-4): (3-5.5); the preparation method comprises the following steps: uniformly mixing the cement, the fly ash, the mineral powder and the coarse aggregate to obtain a primary mixture; adding hydrophobic fibers and filling particles into the primary mixture, uniformly mixing and stirring, finally adding water and a water reducing agent, and uniformly mixing to obtain a mixed material; and pouring and curing the mixed material to obtain a finished product. The water-permeable brick has the advantages of high strength, good water permeability and difficulty in pore blockage after long-time use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of concrete, and more specifically, to a permeable concrete and a preparation method thereof. Background Art

[0002] Permeable concrete is made by mixing cement, water, aggregate and other materials. It has a certain porosity and can be made into concrete pavements, slope protection and their products. It has the effects of drainage, anti-slip, sound absorption, noise reduction and water seepage. It is often used in roads and ground in urban parks, residential areas, stadiums, schools and other places.

[0003] Permeable concrete can reduce the burden on road drainage systems during the rainy season and reduce the impact of heavy rains on cities; it can also regulate the growth of ground plants and soil microorganisms, strengthen the exchange of heat and moisture between the surface and the air, regulate urban climate, reduce surface temperature, and replenish groundwater resources; at the same time, permeable concrete can absorb noise, adsorb urban pollutant dust, and reduce dust pollution.

[0004] However, permeable concrete has a high porosity. During daily use, as time goes by, debris, dust and other materials will clog the pores, affecting the permeability of the permeable concrete and thus affecting the drainage of the permeable concrete.

[0005] Therefore, how to prepare a permeable concrete whose pores are not easily blocked and still have good permeability even after long-term use is a problem to be solved. Summary of the invention

[0006] In order to prepare a permeable concrete whose pores are not easily clogged and which still has good water permeability even after long-term use, the present application provides a permeable concrete and a preparation method thereof.

[0007] In a first aspect, the present application provides a permeable concrete, which adopts the following technical solution: A permeable concrete comprises the following raw materials in parts by weight: 300-400 parts of cement, 1000-1400 parts of coarse aggregate, 80-120 parts of water, 20-40 parts of fly ash, 20-40 parts of mineral powder, 3-4 parts of water reducer, 10-20 parts of hydrophobic fiber and 14-25 parts of filling particles; the filling particles are composed of coated magnesium carbonate, coated slow-release ammonium chloride, hydrophobic zeolite and basalt particles in a mass ratio of 1:1-1.5:2-4:3-5.5.

[0008] By adopting the above technical scheme, cement, coarse aggregate, water, fly ash and mineral powder are combined to construct the skeleton of permeable concrete, and the connection and filling effects of hydrophobic fibers and filling particles are combined to further improve the strength and porosity of permeable concrete, ensuring the permeability while ensuring the strength of concrete.

[0009] Coated magnesium carbonate, coated slow-release ammonium chloride, hydrophobic zeolite and basalt particles are matched together, and the slow release effect of coated magnesium carbonate and coated slow-release ammonium chloride is utilized to avoid the reaction of magnesium carbonate and ammonium chloride with cementitious materials as much as possible, which affects the strength and life of concrete; during the long-term use of permeable concrete, the porosity is easily blocked by dust and impurity particles, but water can still flow. As water contacts the gradually exposed magnesium carbonate during use, the slow dissolution effect of magnesium carbonate in water can be utilized to make the magnesium carbonate gradually dissolve and react with ammonium chloride to generate magnesium chloride soluble in water. The coated magnesium carbonate that originally played a filling effect in the permeable concrete gradually dissolves and flows out of the permeable concrete with water, promoting the discharge of dust and impurity particles from the concrete, ensuring the permeability and porosity of the permeable concrete, so that the pores of the permeable concrete are not easily blocked after long-term use.

[0010] The hydrophobic zeolite, basalt particles and hydrophobic fibers are matched with each other, and the hydrophobic effect of materials such as fibers and zeolite is utilized, and the water-soluble effect of the reaction product of magnesium carbonate and ammonium chloride is combined to ensure that the porosity of the permeable concrete is high while having good water permeability, so that water is not easily stored inside the permeable concrete. Combined with the frost resistance of ammonium chloride, the permeable concrete is not prone to freeze-thaw cracking in winter. Combined with the high strength of the basalt particles and the cross-linked support effect of the hydrophobic fiber network, the strength of the permeable concrete is guaranteed. The network structure formed by the hydrophobic fibers in the concrete, the porous structure of the hydrophobic zeolite, and the particle disappearance effect of the reaction of magnesium carbonate and ammonium chloride are utilized, so that the permeable concrete still has good water permeability after long-term use, and the internal porosity is not easily blocked by dust and impurity particles.

[0011] Preferably, the coated sustained-release ammonium chloride is prepared by coating ammonium chloride particles with a sodium polyacrylate composite film.

[0012] By adopting the above technical scheme, the sodium polyacrylate composite film and the ammonium chloride particles are matched, and the effect of sodium polyacrylate slowly dissolving in water is utilized, so that the ammonium chloride particles can be slowly released in the permeable concrete. After the permeable concrete is used for a long time, the ammonium chloride particles gradually dissolve in water and the ammonium chloride gradually reacts with magnesium carbonate, so that the particle space of the coated magnesium carbonate and the coated ammonium chloride in the original permeable concrete is released, the porosity of the permeable concrete is improved, and the impurity particles and other substances in the permeable concrete can be separated from the permeable concrete, which is not easy to block the pores of the permeable concrete, thereby ensuring the permeability effect of the permeable concrete after long-term use.

[0013] Preferably, the sodium polyacrylate composite film is made of a sodium polyacrylate solution, a sodium alginate solution, lignin and a cross-linking agent in a mass ratio of 1:0.5-1:0.1-0.2:0.02-0.05.

[0014] By adopting the above technical scheme, sodium polyacrylate solution, sodium alginate solution, lignin and a cross-linking agent are matched, and the carboxyl groups in the sodium polyacrylate solution are matched with the carboxyl groups in the sodium alginate solution and the hydroxyl groups on the surface of the lignin, so as to form a cross-linked network structure on the surface of the ammonium chloride particles; the cross-linking bonding effect of sodium polyacrylate, chitosan and cementitious materials is utilized to improve the bonding effect between the coated slow-release ammonium chloride and the cementitious materials, thereby ensuring the strength of the permeable concrete.

[0015] When water circulates during the use of permeable concrete, the slowly water-soluble effect of sodium polyacrylate solution and the water-insolubility of chitosan are used to slowly release ammonium chloride, which reacts with magnesium carbonate to form water-soluble magnesium chloride, thereby ensuring the porosity of the permeable concrete. Lignin can gradually dissolve under the action of alkaline solution, which not only ensures the release of ammonium chloride particles, but also increases the porosity, so that excess particles can be discharged from the blocked pores in the permeable concrete, and the permeability of the permeable concrete can be ensured. In addition, the bonding effect of chitosan and cementitious materials can ensure the strength of the permeable concrete.

[0016] Preferably, the coated magnesium carbonate is prepared by coating magnesium carbonate particles with soybean protein film.

[0017] By adopting the above technical scheme, the soybean protein film is a semi-permeable membrane. With the circulation of water in the permeable concrete and the influence of the hydration temperature, the magnesium carbonate particles can be gradually released, and the slightly soluble effect of the magnesium carbonate particles can gradually dissolve in water and react, so that the original filling position of the magnesium carbonate particles is vacated, thereby improving the internal porosity of the permeable concrete. Even if some dust or particles block the pores, the water-soluble circulation effect of the magnesium carbonate and ammonium chloride products can not only clear the blocked particles, but also enable the permeable concrete to still have a high porosity after a long period of use, thereby ensuring the permeability of the permeable concrete after long-term use.

[0018] Preferably, the soy protein film is made of soy protein liquid, sodium alginate solution, lignin and cross-linking agent in a mass ratio of 1:0.2-0.8:0.1-0.2:0.02-0.1.

[0019] By adopting the above technical scheme, soybean protein liquid, sodium alginate solution and lignin are matched, and the amino and carboxyl groups in the soybean protein liquid are cross-linked and bonded with the carboxyl groups in the sodium alginate solution, and an interwoven network structure is formed on the surface of the magnesium carbonate particles with lignin as the support; sodium alginate is soluble in water, and is easy to dissolve and expose the magnesium carbonate particles during the hydration and water permeability process, and the presence of soybean protein liquid makes it difficult for the coated magnesium carbonate to affect the reaction between cement and water during the mixing process, thereby ensuring the formation of cementitious materials and thus ensuring the strength of permeable concrete; at the same time, the carboxyl groups in sodium alginate are easy to attract and bond with the cementitious materials, thereby improving the bonding effect between the coated magnesium carbonate and the cementitious materials, improving the mechanical strength of the permeable concrete while ensuring the permeability.

[0020] Under the low temperature conditions in the northern winter, the internal pores of permeable concrete are easily frozen, and the soybean protein film is relatively brittle and lignin also has a certain water absorption capacity. The crystallization of low-temperature moisture makes it easy to pierce the soybean protein film. With the circulation of moisture in spring, while ensuring that magnesium carbonate is in contact with moisture, it can also increase the discharge of broken soybean protein film and increase the porosity of permeable concrete, thereby ensuring the permeability of permeable concrete.

[0021] Preferably, the hydrophobic zeolite is prepared by modifying zeolite particles with a silane coupling agent KH-570 and then bonding them with water glass.

[0022] By adopting the above technical scheme, the zeolite particles have adsorptivity, which is convenient for adsorbing the silane coupling agent KH-570. The hydrophobicity of the silane coupling agent KH-570 is utilized to give the zeolite particles a hydrophobic effect, so that while the water in the zeolite particles can flow, it is not easy to retain water in the gaps, and the crystallization of water in winter and the cracking of the permeable concrete can be avoided as much as possible; the water glass on the surface of the hydrophobic zeolite is hydrophilic, which is convenient for attracting water to the surface of the zeolite particles, and the water flows through the pores to ensure water permeability; at the same time, the water glass on the surface of the hydrophobic zeolite can bond with the cementitious material, thereby improving the bonding stability between the hydrophobic zeolite and the cementitious material, the coated magnesium carbonate, and the coated slow-release ammonium chloride, and improving the mechanical strength of the permeable concrete.

[0023] Preferably, the basalt particles are prepared from basalt fine particles and polyvinyl alcohol solution in a mass ratio of 1:0.1-0.4.

[0024] By adopting the above technical scheme, basalt particles and polyvinyl alcohol solution are matched, and the bonding effect of the polyvinyl alcohol solution is utilized to facilitate adhesion to the surface of the basalt particles, and the hydroxyl groups in the polyvinyl alcohol are utilized to facilitate cross-linking and bonding with the cementitious material, coated magnesium carbonate, and coated slow-release ammonium chloride. Combined with the higher strength of the basalt particles, the permeable concrete has higher strength.

[0025] Preferably, the hydrophobic fibers are composed of steel fibers and polyamide-modified asbestos fibers in a mass ratio of 1:0.5-1.

[0026] By adopting the above technical scheme, steel fibers and polyamide modified asbestos fibers are matched with each other, and the connecting effect of steel fibers is utilized to form a network overlap structure in the permeable concrete. In combination with the flexibility and elasticity of polyamide modified asbestos fibers, in the process of flushing the permeable concrete, the particles are promoted to be flushed out of the pores by deformation, and the polyamide fibers do not absorb water, so that moisture is not easily retained in the permeable concrete, which facilitates the flushing of the pores of the permeable concrete and makes it less likely for freeze-thaw cracking to occur inside the permeable concrete.

[0027] Preferably, the polyamide-modified asbestos fiber is prepared by modifying asbestos fiber with methyl silicone oil and then bonding it with a polyacrylamide solution, and the mass ratio of the asbestos fiber to the polyacrylamide solution is 1:0.1-0.3.

[0028] By adopting the above technical scheme, asbestos fiber utilizes its adsorption property to facilitate the adsorption of methyl silicone oil, and utilizes the hydrophobic effect of methyl silicone oil to make asbestos fiber hydrophobic, thereby ensuring that the internal pores of asbestos fiber are not easy to absorb water and expand, and are not easy to crack due to freezing and thawing; utilizing the polyacrylamide solution on the surface of asbestos fiber, not only the flexibility and elasticity are improved, and dust particles in the pores of permeable concrete are facilitated to be flushed during the flushing process, but also the bonding effect between asbestos fiber and cementitious material can be improved, thereby ensuring that the permeable concrete has high strength and good permeability.

[0029] In a second aspect, the present application provides a method for preparing permeable concrete, which adopts the following technical solution: A method for preparing permeable concrete comprises the following steps: S1. Weigh cement, fly ash and mineral powder, mix and stir evenly, then add coarse aggregate and mix and stir evenly to obtain a primary mixture; S2, adding hydrophobic fibers and filling particles to the primary mixture, mixing and stirring evenly, and finally adding water and a water reducing agent, mixing and stirring evenly to obtain a mixed material; S3. The mixed material is poured and cured to obtain a finished permeable concrete.

[0030] By adopting the above technical solution, the finished permeable concrete has high strength and good permeability. Even after being used for a long time, it still has the advantages of pores not being easily blocked and good permeability.

[0031] In summary, this application has the following beneficial effects: 1. The combination of coated magnesium carbonate, coated slow-release ammonium chloride, hydrophobic zeolite and basalt particles can not only improve the strength of permeable concrete, but also as moisture comes into contact with the gradually exposed magnesium carbonate during use, the slow dissolution of magnesium carbonate in water can make the magnesium carbonate gradually dissolve and react with ammonium chloride to generate magnesium chloride soluble in water. The coated magnesium carbonate that originally played a filling effect in the permeable concrete gradually dissolves and flows out of the permeable concrete with water, promoting the discharge of dust and impurity particles from the concrete, ensuring the permeability and porosity of the permeable concrete, so that the pores of the permeable concrete are not easily blocked after long-term use.

[0032] 2. Steel fiber and polyamide modified asbestos fiber are combined, and the connecting effect of steel fiber is utilized to form a network overlap structure in permeable concrete. In combination with the flexibility and elasticity of polyamide modified asbestos fiber, in the process of flushing permeable concrete, the particles are promoted to be flushed out of the pores by deformation. In addition, polyamide fiber does not absorb water, making it difficult for moisture to be retained in the permeable concrete, which facilitates the flushing of the pores of the permeable concrete and prevents freeze-thaw cracking problems from occurring inside the permeable concrete.

[0033] 3. The addition of coated magnesium carbonate and coated slow-release ammonium chloride limits the particle size. Even if the product magnesium chloride dissolves in water and is lost as the permeability time increases, it is not easy to seriously affect the mechanical strength; the steel fibers, zeolite particles and basalt particles that serve as strength support in the permeable concrete are not missing, so after long-term use, the permeable concrete has a higher porosity and higher strength. DETAILED DESCRIPTION

[0034] The present application is further described in detail below with reference to examples.

[0035] Preparation Example of Coated Magnesium Carbonate Preparation Example 1: Coated magnesium carbonate was prepared by the following method: Weigh 1kg of soybean protein liquid, 0.5kg of sodium alginate solution, 0.15kg of lignin, and 0.05kg of a cross-linking agent, mix and stir evenly to prepare a soybean protein composite liquid; the soybean protein liquid is a 2% by mass soy protein isolate aqueous solution; the sodium alginate solution is a 1% by mass sodium alginate aqueous solution; the average particle size of the lignin is 5 μm, and the cross-linking agent is glutaraldehyde; 0.5 kg of soybean protein compound liquid is evenly sprayed on the surface of 1 kg of magnesium carbonate particles, and the spraying speed of the soybean protein compound liquid is 60 g / min. During the spraying process, the magnesium carbonate particles are stirred at a speed of 120 r / min. After being evenly mixed, they are dried and dispersed until the magnesium carbonate particles do not stick to each other and agglomerate. The soybean protein compound liquid forms a soybean protein film on the surface of the magnesium carbonate particles to obtain a finished coated magnesium carbonate; the coated magnesium carbonate is sieved through a 300-mesh sieve.

[0036] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 1 kg of soybean protein liquid, 0.2 kg of sodium alginate solution, 0.1 kg of lignin and 0.02 kg of cross-linking agent were weighed and mixed evenly to prepare a soybean protein composite liquid; the soybean protein liquid was a 2% by mass aqueous solution of soybean protein isolate; the sodium alginate solution was a 1% by mass aqueous solution of sodium alginate; the average particle size of lignin was 5 μm, and the cross-linking agent was glutaraldehyde.

[0037] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 1 kg of soybean protein liquid, 0.8 kg of sodium alginate solution, 0.2 kg of lignin and 0.1 kg of cross-linking agent were weighed and mixed and stirred evenly to prepare a soybean protein composite liquid; the soybean protein liquid was a 2% by mass aqueous solution of soybean protein isolate; the sodium alginate solution was a 1% by mass aqueous solution of sodium alginate; the average particle size of lignin was 5 μm, and the cross-linking agent was glutaraldehyde.

[0038] Preparation Example of Coated Sustained Release Ammonium Chloride Preparation Example 4: Coated sustained-release ammonium chloride is prepared by the following method: Weigh 1 kg of sodium polyacrylate solution, 0.8 kg of sodium alginate solution, 0.15 kg of lignin and 0.04 kg of cross-linking agent, mix and stir evenly to prepare a sodium polyacrylate composite solution; the mass fraction of the sodium polyacrylate solution is 1%; the sodium alginate solution is a sodium alginate aqueous solution with a mass fraction of 1%, the average particle size of the lignin is 3 μm, and the cross-linking agent is glutaraldehyde; 0.6 kg of sodium polyacrylate composite liquid is evenly sprayed on the surface of 1 kg of ammonium chloride particles, and the spraying speed of the sodium polyacrylate composite liquid is 60 g / min. During the spraying process, the ammonium chloride particles are stirred at a speed of 120 r / min. After being evenly mixed, they are dried and dispersed until the ammonium chloride particles do not stick to each other and agglomerate. The sodium polyacrylate composite liquid forms a sodium polyacrylate composite film on the surface of the ammonium chloride particles to obtain a finished coated slow-release ammonium chloride; and the finished product is passed through a 300-mesh sieve.

[0039] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1 kg sodium polyacrylate solution, 0.5 kg sodium alginate solution, 0.1 kg lignin and 0.02 kg cross-linking agent were weighed and mixed evenly to prepare a sodium polyacrylate composite solution; the mass fraction of the sodium polyacrylate solution was 1%; the sodium alginate solution was a sodium alginate aqueous solution with a mass fraction of 1%, the average particle size of the lignin was 3 μm, and the cross-linking agent was glutaraldehyde.

[0040] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1 kg sodium polyacrylate solution, 1 kg sodium alginate solution, 0.2 kg lignin and 0.05 kg cross-linking agent were weighed and mixed evenly to prepare a sodium polyacrylate composite solution; the mass fraction of the sodium polyacrylate solution was 1%; the sodium alginate solution was a sodium alginate aqueous solution with a mass fraction of 1%, the average particle size of the lignin was 3 μm, and the cross-linking agent was glutaraldehyde.

[0041] Preparation Example of Hydrophobic Zeolite Preparation Example 7: Hydrophobic zeolite is prepared by the following method: 10 kg of zeolite particles were placed in 100 kg of silane coupling agent KH-570 and stirred and dispersed at a stirring speed of 350 r / min. After stirring for 20 minutes, the zeolite particles were separated by filtration, and then evenly sprayed with 1.5 kg of water glass. After drying and dispersion until the zeolite particles did not stick to each other and agglomerate, a finished hydrophobic zeolite was obtained.

[0042] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 10 kg of zeolite particles were placed in 100 kg of silane coupling agent KH-570 and stirred and dispersed at a stirring speed of 350 r / min. After stirring for 20 minutes, the zeolite particles were separated by filtration, and then evenly sprayed with 1 kg of water glass. After drying and dispersion until the zeolite particles did not stick to each other and agglomerate, a finished hydrophobic zeolite was obtained.

[0043] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 10 kg of zeolite particles were placed in 100 kg of silane coupling agent KH-570 and stirred and dispersed at a stirring speed of 350 r / min. After stirring for 20 minutes, the zeolite particles were separated by filtration, and then evenly sprayed with 2 kg of water glass. After drying and dispersion until the zeolite particles did not stick to each other and agglomerate, a finished hydrophobic zeolite was obtained.

[0044] Preparation example of basalt particles Preparation Example 10: Basalt particles are prepared by the following method: 0.25 kg of polyvinyl alcohol solution was uniformly sprayed on the surface of 1 kg of basalt particles, the polyvinyl alcohol solution was a 1% polyvinyl alcohol aqueous solution, the average particle size of the basalt particles was 80 μm, and the basalt particles were dried and dispersed until they did not stick to each other and agglomerated, thereby obtaining finished basalt particles.

[0045] Preparation Example 11: This preparation example differs from Preparation Example 10 in that: 0.1 kg of polyvinyl alcohol solution was uniformly sprayed on the surface of 1 kg of basalt particles, the polyvinyl alcohol solution was a 1% polyvinyl alcohol aqueous solution, the average particle size of the basalt particles was 80 μm, and the basalt particles were dried and dispersed until they did not stick to each other and agglomerated, thereby obtaining finished basalt particles.

[0046] Preparation Example 12: This preparation example differs from Preparation Example 10 in that: 0.4 kg of polyvinyl alcohol solution was uniformly sprayed on the surface of 1 kg of basalt particles, the polyvinyl alcohol solution was a 1% polyvinyl alcohol aqueous solution, the average particle size of the basalt particles was 80 μm, and the basalt particles were dried and dispersed until they did not stick to each other and agglomerated, thereby obtaining finished basalt particles.

[0047] Preparation example of hydrophobic polyamide modified asbestos fiber Preparation Example 13: Hydrophobic polyamide modified asbestos fiber is prepared by the following method: Weigh 1 kg of asbestos fiber and soak and disperse it in 10 kg of methyl silicone oil at a stirring speed of 200 r / min. The average length of the asbestos fiber is 3 mm, thereby obtaining hydrophobic asbestos fiber. 0.2 kg of polyacrylamide solution was uniformly sprayed on the surface of 1 kg of hydrophobic asbestos fiber, wherein the polyacrylamide solution was a 1% by mass polyamide aqueous solution, and the solution was dried and dispersed until the hydrophobic asbestos fibers did not stick to each other and agglomerated, thereby obtaining a finished polyamide modified asbestos fiber.

[0048] Preparation Example 14: This preparation example differs from Preparation Example 13 in that: 0.1 kg of polyacrylamide solution was uniformly sprayed on the surface of 1 kg of hydrophobic asbestos fiber, wherein the polyacrylamide solution was a polyamide aqueous solution with a mass fraction of 1%, and the solution was dried and dispersed until the hydrophobic asbestos fibers did not stick to each other and agglomerated, thereby obtaining a finished polyamide modified asbestos fiber.

[0049] Preparation Example 15: This preparation example differs from Preparation Example 13 in that: 0.3 kg of polyacrylamide solution was uniformly sprayed on the surface of 1 kg of hydrophobic asbestos fiber, wherein the polyacrylamide solution was a polyamide aqueous solution with a mass fraction of 1%, and the solution was dried and dispersed until the hydrophobic asbestos fibers did not stick to each other and agglomerated, thereby obtaining a finished polyamide modified asbestos fiber. Example

[0050] Example 1: A permeable concrete; 360kg cement, 1200kg coarse aggregate, 100kg water, 30kg fly ash, 30kg mineral powder, 3.6kg water reducer, 15kg hydrophobic fiber, 20kg filling particles; the hydrophobic fiber is composed of steel fiber and polyamide modified asbestos fiber prepared in Preparation Example 13 in a mass ratio of 1:0.8; the filling particles are composed of coated magnesium carbonate prepared in Preparation Example 1, coated slow-release ammonium chloride prepared in Preparation Example 4 in a mass ratio of 1:1:3:5. , the hydrophobic zeolite prepared in Preparation Example 7 and the basalt particles prepared in Preparation Example 10; the cement is silicate cement with a P.O42.5, the coarse aggregate is continuously graded crushed stone, and the crushed stone particle size is 5-20mm; the fly ash is F class II fly ash, the fineness of the fly ash (45μm square hole sieve residue) is 8%, the loss on ignition is less than 4.5%, the water requirement ratio is less than 96%, and the water content is less than 0.2%; the mineral powder is S95 grade slag powder, and the density is 2.8g / cm 3 , with a specific surface area of ​​420m 2 / kg, activity index (7d) is 82%, activity index (28d) is 94%, fluidity ratio is 96%, water content is 0.2%; water reducer is polycarboxylic acid high efficiency water reducer; The preparation method is as follows: S1. Weigh cement, fly ash and mineral powder, mix and stir evenly, then add coarse aggregate and mix and stir evenly to obtain a primary mixture; S2, adding hydrophobic fibers and filling particles to the primary mixture, mixing and stirring evenly, and finally adding water and a water reducing agent, mixing and stirring evenly to obtain a mixed material; S3. The mixed material is poured and cured to obtain a finished permeable concrete.

[0051] Embodiment 2: This embodiment differs from Embodiment 1 in that: 300kg cement, 1000kg coarse aggregate, 80kg water, 20kg fly ash, 20kg mineral powder, 3kg water reducer, 10kg hydrophobic fiber, 14kg filling particles; the hydrophobic fiber is composed of steel fiber and polyamide modified asbestos fiber prepared in Preparation Example 14 in a mass ratio of 1:0.5; the filling particles are composed of coated magnesium carbonate prepared in Preparation Example 2, coated slow-release ammonium chloride prepared in Preparation Example 5, hydrophobic zeolite prepared in Preparation Example 8 and basalt particles prepared in Preparation Example 11 in a mass ratio of 1:1:2:3.

[0052] Embodiment 3: This embodiment differs from Embodiment 1 in that: 400kg cement, 1400kg coarse aggregate, 120kg water, 40kg fly ash, 40kg mineral powder, 4kg water reducer, 20kg hydrophobic fiber, 25kg filling particles; the hydrophobic fiber is composed of steel fiber and polyamide modified asbestos fiber prepared in Preparation Example 15 in a mass ratio of 1:1; the filling particles are composed of coated magnesium carbonate prepared in Preparation Example 3, coated slow-release ammonium chloride prepared in Preparation Example 6, hydrophobic zeolite prepared in Preparation Example 9 and basalt particles prepared in Preparation Example 12 in a mass ratio of 1:1.5:4:5.5.

[0053] Embodiment 4: This embodiment differs from Embodiment 1 in that: In the preparation process of coated magnesium carbonate, the sodium polyacrylate complex liquid is replaced by an equal mass of sodium alginate solution, and in the preparation process of coated sustained-release ammonium chloride, the soybean protein complex liquid is replaced by an equal mass of sodium alginate solution.

[0054] Embodiment 5: This embodiment differs from Embodiment 1 in that: In the preparation process of coated magnesium carbonate, no sodium alginate solution and lignin were added; in the preparation process of coated slow-release ammonium chloride, no sodium alginate solution and lignin were added.

[0055] Embodiment 6: This embodiment differs from Embodiment 1 in that: No water glass was added during the preparation of the hydrophobic zeolite.

[0056] Embodiment 7: This embodiment differs from Embodiment 1 in that: During the preparation of basalt microparticles, no polyvinyl alcohol solution was added.

[0057] Embodiment 8: This embodiment differs from Embodiment 1 in that: In the process of preparing the hydrophobic fiber, the polyamide modified asbestos fiber is replaced by the hydrophobic asbestos fiber of the same mass, that is, the hydrophobic asbestos fiber is prepared as follows: 1 kg of asbestos fiber is weighed and immersed and dispersed in 10 kg of methyl silicone oil at a stirring speed of 200 r / min. The average length of the asbestos fiber is 3 mm, and the hydrophobic asbestos fiber is obtained.

[0058] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: The filling particles are basalt particles and zeolite particles. The average particle size of the basalt particles is 200 μm, and the average particle size of the zeolite particles is 100 μm, both of which are commonly available on the market.

[0059] Comparative Example 2: The difference between this comparative example and Example 1 is that: No coated magnesium carbonate and coated slow-release ammonium chloride were added to the filling particles.

[0060] Comparative Example 3: The difference between this comparative example and Example 1 is that: No coated slow-release ammonium chloride was added to the filled granules.

[0061] Comparative Example 4: The difference between this comparative example and Example 1 is that: The hydrophobic fibers in the raw materials are replaced by asbestos fibers of equal mass, and the filling particles are replaced by zeolite of equal mass.

[0062] Performance testing 1. Compressive strength test The 28d compressive strength of the permeable concrete prepared in Examples 1-8 and Comparative Examples 1-4 was tested using the GB / T50081-2019 concrete physical and mechanical properties test method standard.

[0063] 2. Water permeability test The water permeability coefficient of the permeable concrete prepared in Examples 1-3 and Comparative Examples 1-3 was tested using the water permeability coefficient testing method in JC / T945-2005 permeable bricks.

[0064] 3. Porosity detection The porosity of the concrete prepared in Examples 1-8 and Comparative Examples 1-3 was tested using CJJ / T135-2009 Technical Specification for Permeable Concrete Pavement. After the permeable concrete was used for one year, the porosity was tested again and the porosity difference was recorded, where porosity difference = initial porosity - porosity after one year.

[0065] 4. Freeze resistance test The frost resistance of the concrete prepared in Examples 1-3 and Comparative Example 4 was tested using CJJ / T135-2009 Technical Specification for Permeable Concrete Pavement, and the compressive strength loss rate after 25 freeze-thaw cycles was recorded, and the data was recorded.

[0066] In the following table, “ / ” means that the corresponding embodiment or comparative example was not tested for the item, so there is no data.

[0067] Table 1 Performance test table It can be seen from Examples 1-3 and Table 1 that the permeable concrete prepared in the present application has high compressive strength and good water permeability. After a long period of use, the porosity difference is small, and the larger the porosity difference, the more blocked pores there are; and the pores are not easily blocked, which can ensure good water permeability. Even under freeze-thaw cycles, the loss rate is low, indicating good frost resistance.

[0068] In combination with Example 1 and Examples 4-8 and Table 1, it can be seen that in the preparation process of coated magnesium carbonate in Example 4, the sodium polyacrylate composite liquid is replaced by an equal mass of sodium alginate solution, and in the preparation process of coated slow-release ammonium chloride, the soybean protein composite liquid is replaced by an equal mass of sodium alginate solution. Compared with Example 1, the compressive strength of the permeable concrete prepared in Example 4 is lower than that in Example 1, and the porosity difference is greater than that in Example 1; it indicates that the slow release of the coated slow-release ammonium chloride is not easy to affect the amount of mixing water, and in the permeable process, it gradually contacts with water, thereby ensuring the reaction of ammonium chloride and magnesium carbonate, so that the permeable concrete still has a high porosity after long-term use to meet the permeability.

[0069] In the preparation process of coated magnesium carbonate in Example 5, sodium alginate solution and lignin were not added; in the preparation process of coated slow-release ammonium chloride, sodium alginate solution and lignin were not added. Compared with Example 1, the compressive strength of the permeable concrete prepared in Example 5 was lower than that in Example 1, and the porosity difference was greater than that in Example 1; this indicates that the cross-linking bonding effect of sodium polyacrylate, chitosan and cementitious materials is utilized to improve the bonding effect of coated slow-release ammonium chloride and cementitious materials, thereby ensuring the strength of the permeable concrete. Lignin can be gradually dissolved under the action of alkaline solution, which ensures the release effect of ammonium chloride particles while increasing the porosity, so that the blocked pores in the permeable concrete can discharge excess particles, and also ensure the permeability of the permeable concrete.

[0070] No water glass was added during the preparation of the hydrophobic zeolite in Example 6. Compared with Example 1, the compressive strength of the permeable concrete prepared in Example 6 was lower than that in Example 1, and the porosity difference was greater than that in Example 1; this indicates that the water glass on the surface of the zeolite is hydrophilic, which facilitates the attraction of moisture to the surface of the zeolite particles, and the moisture flows through the pores to ensure water permeability; at the same time, the water glass on the surface of the hydrophobic zeolite can bond with the cementitious material, thereby improving the bonding stability between the hydrophobic zeolite and the cementitious material, coated magnesium carbonate, and coated slow-release ammonium chloride, and improving the mechanical strength of the permeable concrete.

[0071] In the preparation process of basalt particles in Example 7, no polyvinyl alcohol solution was added. Compared with Example 1, the compressive strength of the permeable concrete prepared in Example 7 was lower than that in Example 1, and the porosity difference was greater than that in Example 1. This indicates that the bonding effect of the polyvinyl alcohol solution is convenient for adhering to the surface of the basalt particles, and the hydroxyl groups in the polyvinyl alcohol are convenient for cross-linking and bonding with the cementitious material, coated magnesium carbonate, and coated slow-release ammonium chloride. Combined with the higher strength of the basalt particles, the permeable concrete has higher strength.

[0072] In the preparation process of hydrophobic fibers in Example 8, hydrophobic asbestos fibers of equal mass are used to replace polyamide-modified asbestos fibers. Compared with Example 1, the compressive strength of the permeable concrete prepared in Example 8 is lower than that in Example 1, and the porosity difference is greater than that in Example 1. This shows that polyacrylamide can not only improve the bonding effect between asbestos fibers and cementitious materials and improve the strength of permeable concrete, but also utilize its flexibility and elasticity to wash away dust particles in the pores of the permeable concrete during rainwater scouring, so that the permeable concrete still has a high porosity after a long period of use, thereby having a better permeable effect.

[0073] Combining Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that the filling particles in Comparative Example 1 are basalt particles and zeolite particles. Compared with Example 1, the compressive strength of the permeable concrete prepared in Comparative Example 1 is lower than that in Example 1, the water permeability coefficient is lower than that in Example 1, and the porosity difference is greater than that in Example 1; this indicates that the hydrophobic zeolite can be combined with the basalt particles treated with polyvinyl alcohol, the coated magnesium carbonate and the coated slow-release ammonium chloride, which can not only improve the porosity of the permeable concrete, but also improve the bonding effect between the filling particles and the cementitious material, thereby improving the strength of the permeable concrete.

[0074] In Comparative Example 2, no coated magnesium carbonate and coated slow-release ammonium chloride were added to the filling particles, and in Comparative Example 3, no coated slow-release ammonium chloride was added to the filling particles. Compared with Example 1, the compressive strength of the permeable concrete prepared in Comparative Examples 2 and 3 was lower than that in Example 1, the water permeability coefficient was lower than that in Example 1, and the porosity difference was greater than that in Example 1; this indicates that the slow dissolution effect of magnesium carbonate in water can make the magnesium carbonate gradually dissolve and react with ammonium chloride to generate magnesium chloride that is soluble in water, and the coated magnesium carbonate that originally played a filling effect in the permeable concrete gradually dissolves and flows out of the permeable concrete with water, thereby promoting the discharge of dust and impurity particles from the concrete, ensuring the permeability and porosity of the permeable concrete, so that the pores of the permeable concrete are not easily blocked after long-term use.

[0075] In the raw materials of Comparative Example 4, the hydrophobic fiber is replaced by the same mass of asbestos fiber, and the filling particles are replaced by the same mass of zeolite. Compared with Example 1, the compressive strength of the permeable concrete prepared in Comparative Example 4 is lower than that in Example 1, and the strength loss rate after freeze-thaw is greater than that in Example 1; this indicates that the water-absorbing fiber and the water-absorbing zeolite are convenient for absorbing water in the pores of the permeable concrete. As the freezing progresses, the pores inside the concrete become larger and larger, resulting in the strength of the concrete being affected.

[0076] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A permeable concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 300-400 parts of cement, 1000-1400 parts of coarse aggregate, 80-120 parts of water, 20-40 parts of fly ash, 20-40 parts of mineral powder, 3-4 parts of water reducer, 10-20 parts of hydrophobic fiber and 14-25 parts of filling particles; the filling particles are composed of coated magnesium carbonate, coated slow-release ammonium chloride, hydrophobic zeolite and basalt particles in a mass ratio of 1:1-1.5:2-4:3-5.

5.

2. The permeable concrete according to claim 1, characterized in that: The coated sustained-release ammonium chloride is prepared by coating ammonium chloride particles with a sodium polyacrylate composite film.

3. The permeable concrete according to claim 2, characterized in that: The sodium polyacrylate composite film is made of a sodium polyacrylate solution, a sodium alginate solution, lignin and a cross-linking agent in a mass ratio of 1:0.5-1:0.1-0.2:0.02-0.

05.

4. The permeable concrete according to claim 1, characterized in that: The coated magnesium carbonate is prepared by coating magnesium carbonate particles with soybean protein films.

5. The permeable concrete according to claim 4, characterized in that: The soybean protein film is prepared from soybean protein liquid, sodium alginate solution, lignin and a cross-linking agent in a mass ratio of 1:0.2-0.8:0.1-0.2:0.02-0.

1.

6. The permeable concrete according to claim 1, characterized in that: The hydrophobic zeolite is prepared by bonding water glass after zeolite particles are modified by silane coupling agent KH-570, and the mass ratio of zeolite particles to water glass is 10:1-2.

7. The permeable concrete according to claim 1, characterized in that: The basalt particles are prepared from basalt particles and polyvinyl alcohol solution in a mass ratio of 1:0.1-0.

4.

8. The permeable concrete according to claim 1, characterized in that: The hydrophobic fibers are composed of steel fibers and polyamide modified asbestos fibers in a mass ratio of 1:0.5-1.

9. The permeable concrete according to claim 8, characterized in that: The polyamide-modified asbestos fiber is prepared by bonding asbestos fiber with polyacrylamide solution after being modified with methyl silicone oil, and the mass ratio of asbestos fiber to polyacrylamide solution is 1:0.1-0.

3.

10. A method for preparing permeable concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh cement, fly ash and mineral powder, mix and stir evenly, then add coarse aggregate and mix and stir evenly to obtain a primary mixture; S2, adding hydrophobic fibers and filling particles to the primary mixture, mixing and stirring evenly, and finally adding water and a water reducing agent, mixing and stirring evenly to obtain a mixed material; S3. The mixed material is poured and cured to obtain a finished permeable concrete.